Risk of behavioural and emotional disorders in Lithuanian school aged children as assessed with SDQ during the second lockdown due to COVID-19 - Jusienė, Roma; Baukienė, Edita; Breidokienė, Rima (Psichologija, 2021)
As a result of the outbreak of COVID-19 and consequent restrictions, the distance education was introduced in Lithuania in 2020 spring (the first lockdown, lasted for around 3 months) and 2020 autumn (the second lockdown, still lasting, June 2021). The prevalence of children’s mental health problems during the first lockdown was similar to pre-epidemic rates in Lithuania, but the prolonged lockdown (and therefore school closure) might have more negative consequences on children’s mental health. This study aimed to reveal the incidence of mental health problems as rated by parents with a Strengths and Difficulties Questionnaire during the second lockdown in school aged children. This research sample included data of 514 children (46% girls), aged 7 to 14 years old (mean age 10.15 years, SD = 3.47). The children’s mental health problems were assessed using a Lithuanian version of the Strengths and Difficulties Questionnaire, parental form, in April–May 2021. Results revealed that 29.6% of Lithuanian children had scores in the clinical (abnormal) range of emotional problems and 21.6% – of conduct problems. Based on total difficulties score, 31.6% of children get in clinical range of emotional and behavioural problems, as rated by parents by the end of the second lockdown. The results are compared to pre-pandemic epidemiological rates of emotional and behavioural problems reported and those documented after the first quarantine in Lithuania and highlight important findings for professionals and policy makers about the detrimental effects of prolonged lockdown and school closure on children’s mental health.
Keywords: emotional and behavioral problems; SDQ; children; lockdown; COVID-19